Perbedaan Kemampuan Berpikir Kreatif Pembelajaran Daring Melalui Implementasi Multimedia Collaborative-Interactive (Co-Interactive) pada Masa Pandemi - T.S. Hadi; Indri Lestari; Ami Fidianty; Wian Azrilia (Institut Agama Islam Negeri Curup, 2022)
The research was conducted during the covid-19 pandemic and learning was carried out from and there were many technical obstacles and students' thinking abilities which tended to be low because they were unable to understand the material by being given in the form of modules only. During a pandemic, learning is carried out at home to avoid transmission. With this, educators must move actively so that learning can still be given. So that learning is needed with the help of interactive collaborative multimedia with the help of Learning Management Systems (LMS), zoom meetings, and YouTube as learning multimedia. Learning with zoom meetings to provide direct explanations to students about the material being studied. YouTube is given as a multimedia-based learning because students can see learning using videos. The research method used is an experiment with two classes, namely the experimental class and the control class as a comparison with conventional learning. The results obtained that there is an average difference between students with learning using interactive multimedia collaborative better than students with conventional learning.